Paediatrics: how to manage acute asthma exacerbations - James S Leung (BioExcel Publishing Ltd, 2021)
Background: Asthma is the most common chronic disease of childhood and a major source of childhood health burden worldwide. These burdens are particularly marked when children experience characteristic 'symptom flare-ups' or acute asthma exacerbations (AAEs). AAE are associated with significant health and economic impacts, including acute Emergency Department visits, occasional hospitalizations, and rarely, death. To treat children with AAE, several medications have been studied and used. Methods: We conducted a narrative review of the literature with the primary objective of understanding the evidence of their efficacy. We present this efficacy evidence in the context of a general stepwise management pathway for paediatric AAEs. This framework is developed from the combined recommendations of eight established (inter)national paediatric guidelines. Discussion: Management of paediatric AAE centres around four major care goals: (1) immediate and objective assessment of AAE severity; (2) prompt and effective medical interventions to decrease respiratory distress and improve oxygenation; (3) appropriate disposition of patient; and (4) safe discharge plans. Several medications are currently recommended with varying efficacies, including heliox, systemic corticosteroids, first-line bronchodilators (salbutamol/albuterol), adjunctive bronchodilators (ipratropium bromide, magnesium sulfate) and second-line bronchodilators (aminophylline, i.v. salbutamol, i.v. terbutaline, epinephrine, ketamine). Care of children with AAE is further enhanced using clinical severity scoring, pathway-driven care and after-event discharge planning. Conclusions: AAEs in children are primarily managed by medications supported by a growing body of literature. Continued efforts to study the efficacy of second-line bronchodilators, integrate AAE management with long-term asthma control and provide fair/equitable care are required.